EFFECTIVENESS OF ONLINE LEARNING AS A FORM OF INDEPENDENT LEARNING AT NAHDLATUL ULAMA UNIVERSITY BLITAR - Saptono Hadi; Nur Arqom Eka Fatria; Yusniarsi Primasari (Universitas Islam Balitar, 2023)
Technology and communication sciences have developed rapidly in all lines and fields, including the impact on educational institutions, as well as higher education as one of the producers of human resource products. Previously, learning had to focus on limited space, so in the millennial century, learning has changed the direction of cooperative learning according to user needs. Learners do civitas learning activities can be taken anytime, anywhere, even with whom it can be done. Online learning, the effectiveness of online models is a solution step. Technical precision, model, the right method effective innovative that bring change. The implementation of these fundamental changes has made the education system in Indonesia undergo a multi-change process. Actions are needed as a reform step in all areas of access to education as a point of achievement of national education goals. The research aims to determine the effectiveness of online learning (Online Learning Model) in an effort to realize the independence of higher institutions. The subject of study is the students of the Faculty of Education and Social Sciences, Nahdlatul Ulama University, Blitar. The research approach applies qualitative, data collection is carried out by interviews/questionnaires and questionnaires. It was found that online learning had a significant impact, especially when there was an increase in technological skills, a change in mindset, and an increase in language skills. There are weaknesses in personality control in the seriousness of attending lectures, the process of learning activities provides difficulties and experiences delays in study responses.